Participation of adolescents in household decision-making process in Bangladesh - Rahman Mizanur; Kabir M; Shahidullah M (Wolters Kluwer Medknow Publications, 2007)
Background: The decision-making authority is one of the ways of measuring the female empowerment, although mere participation in any matter does not corroborate full empowerment of women. However, participation in decision-making process in household matters considers that a female is accounted in the family. Objective: The present study investigated to the extent at which the female adolescents participated in decision-making process in household matters and assessed the factors influencing them. Study Setting: Both rural and urban areas of Bangladesh. Study Design: A quantitative and a qualitative study designs were adopted for this study. Sample Size and Sampling: A cluster sampling technique was used to select the sample. A sample of 3362 female adolescents irrespective of their marital status was selected using a cluster sampling technique. To complement the results found in quantitative analysis, a series of focus group discussions were also conducted among the adolescents. Results: The analysis revealed that a large proportion of the study adolescents did not participate in any decision-making process in their household matters. Only about one-third (31.1%) of the adolescents participated in any household matter; however, the acceptance of their opinions was minimal. In spite of little participation of adolescents in family matters, multivariate logistic regression analysis revealed that older adolescents aged 15-19 years, years of schooling, work status, and the family members with a positive attitude toward female education appeared to be the influencing factors for adolescent participation in household affairs ( P < 0.05 ). Conclusions : The study concluded that gainful economic activities of adolescents and female education are the key elements for participation of female adolescents in different household matters.